Familial and individual reasons for student dropout: Schools’ perception - Videnović Marina; Lazarević Ljiljana 0000-0003-1629-3699 (Psihološka Istraživanja, 2017)
The main objective of the research was to identify individual and familial factors students cite as the reasons for dropping out of school or being at the risk of doing so. We interviewed a total of twelve students who dropped out of school or are at the risk of dropping out of primary (six students) or secondary school (six students) and four parents. A semi-structured interview was used. We singled out four categories of students, determined by their perception of the reasons for dropping out of school. Those categories included: underage pregnancy, assuming a parental role, problematic behaviour (thefts, fights) and weak motivation for school and learning. It seems justified to look for a typology of dropout cases since each of the selected groups of students requires specific preventive measures in order to secure continuation of their education. Furthermore, research has shown that, when it comes to their children dropping out of school, parents tend to blame the child’s character traits they deem unchangeable. The failure of school staff to help the child further encourages this belief in parents.